Evolutionary Musicology Meets Embodied Cognition: Biocultural Coevolution and the Enactive Origins of Human Musicality - van der Schyff, Dylan; Schiavio, Andrea (Frontiers in Neuroscience, 2017)
Despite evolutionary musicology's interdisciplinary nature, and the diverse methods it employs, the field has nevertheless tended to divide into two main positions. Some argue that music should be understood as a naturally selected adaptation, while others claim that music is a product of culture with little or no relevance for the survival of the species. We review these arguments, suggesting that while interesting and well-reasoned positions have been offered on both sides of the debate, the nature-or-culture (or adaptation vs. non-adaptation) assumptions that have traditionally driven the discussion have resulted in a problematic either/or dichotomy. We then consider an alternative “biocultural” proposal that appears to offer a way forward. As we discuss, this approach draws on a range of research in theoretical biology, archeology, neuroscience, embodied and ecological cognition, and dynamical systems theory (DST), positing a more integrated model that sees biological and cultural dimensions as aspects of the same evolving system. Following this, we outline the enactive approach to cognition, discussing the ways it aligns with the biocultural perspective. Put simply, the enactive approach posits a deep continuity between mind and life, where cognitive processes are explored in terms of how self-organizing living systems enact relationships with the environment that are relevant to their survival and well-being. It highlights the embodied and ecologically situated nature of living agents, as well as the active role they play in their own developmental processes. Importantly, the enactive approach sees cognitive and evolutionary processes as driven by a range of interacting factors, including the socio-cultural forms of activity that characterize the lives of more complex creatures such as ourselves. We offer some suggestions for how this approach might enhance and extend the biocultural model. To conclude we briefly consider the implications of this approach for practical areas such as music education.